The Importance of Trust for Investment: Evidence from Venture Capital - Laura Bottazzi; Marco Da Rin; Thomas Hellmann (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
This paper examines the effect of trust in a micro-economic environment, where trust is clearly exogenous. Using a hand-collected data on European venture capital, we show that the Eurobarometer measure of trust among nations significantly affects investment decisions. This holds even after controlling for investor and company fixed effects, geographic distance, information and transaction costs. The national identity of venture capital firms' partners is shown to matter for the effect of trust. We also considers the relationship between trust and sophisticated contracts involving contingent control rights. We find trust and sophisticated contracts to be complements, not substitutes.
Keywords: 330; Risikokapital; Unternehmensfinanzierung; Vertrauen; Verhaltensökonomik; Theorie